José María Margas: university reform in Caracas 1827-1829, medicine and public health (Revista Venezolana de Salud Pública, 2016)
The object of the present work of documentary and bibliographic research is to reconstruct the academic and administrative process carried out by Jose Maria Vargas at the Central University in Caracas during the period 1827-1829 upon the implementation of the Decree on the reorganization of this University signed by Simón Bolívar on June 24, 1827.  In this set of changes, the creation of the Anatomy Chair at the university is examined as part of the curriculum reform for the formation of the doctor.  The importance of the Chair is emphasized because it constituted the essential unit that organized the university teaching work to grant the academic degrees of Senior, Bachelor, Master and Doctor in the professions of Medicine, Laws and Theology by then.   In this order of ideas, aspects of the University reform including the issue of public health are identified as part of the preparation of the doctor. Written evidence is left of this documentary review about the projection and scope of the lectures conducted by Vargas when showing partial data of his disciples and with them cognitive and social institutionalization of Medicine in Venezuela during the nineteenth century.
Keywords: Heald; Public; Venezuela